Cellulose Separators With Integrated Carbon Nanotube Interlayers for Lithium-Sulfur Batteries: An Investigation into the Complex Interplay between Cell Components. Issue 14 (24th September 2019) - Chien, Yu-Chuan; Pan, Ruijun; Lee, Ming-Tao; Nyholm, Leif; Brandell, Daniel; Lacey, Matthew J.
Abstract : This work aims to address two major roadblocks in the development of lithium-sulfur (Li-S) batteries: the inefficient deposition of Li on the metallic Li electrode and the parasitic "polysulfide redox shuttle". These roadblocks are here approached, respectively, by the combination of a cellulose separator with a cathode-facing conductive porous carbon interlayer, based on their previously reported individual benefits. Both approaches result in significant improvements in cycle life in test cells with positive electrodes with practically relevant specifications. Despite the substantially prolonged cycle life, the combination of the interlayer and cellulose separator generates an increase in polysulfide shuttle current, leading to greatly reduced Coulombic efficiency. Based on XPS analyses, the latter is ascribed to a change in the composition of the solid electrolyte interphase (SEI) on the Li electrode. At the same time, the rate of electrolyte decomposition is found to be lower in cells with cellulose-based separators, which corroborates the observation of longer cycle life. These seemingly contradictory and counterintuitive observations demonstrate the complicated interactions between the cell components in the Li-S system and how strategies aiming to mitigate one unwanted process may exacerbate another. This study demonstrates the value of a holistic approach to the development of Li-S chemistry.